Pharmacist: A Healthcare Professional Serving as Frontline Warrior Completely Overlooked - Shankar, Ravi; Kumar, Manish; Upadhyay, Prabhat Kumar (Indian Journal of Pharmaceutical Education and Research, 2023)
During the tough times of SARS-CoV-2 (COVID-19), the pharmacy professionals played a significant role by providing their services at various working stations and levels including hospitals, private clinics, community pharmacies, nursing homes, pharmaceutical industries, CROs and various health care programmes. However, the services provided by pharmacists were seldom mentioned and the professionals were not recognized as first line health care professional. The media, authorities and even general public have failed to appreciate the efforts of the pharmacy professionals as a part of essential healthcare team during the disaster. This review is focussed upon the contributions of pharmacists in patient care, healthcare services, patient care and well-being of the public during the COVID-19 pandemic. The various important tasks and roles played by pharmacist are described in the literature which have highly contributed towards a safer and healthier world. We hope that after going through the review and after having the idea about the roles and responsibilities that the pharmacist has played during COVID-19 will change the perspective of the people and the efforts of pharma professionals will be appreciated and recognized.
Keywords: Coronavirus; Global health; Pandemic; Pharmacists; Pharmacy